PENGARUH PROMOSI, LOKASI, DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK JASA LAUNDRY DI LINA LAUNDRY BATAM - Simanjuntak, Yuni; Wasiman, Wasiman (SCIENTIA JOURNAL, 2025)
This research examines the influence of promotion, location, and facilities on customer purchase decisions at Lina Laundry in Batam. With increasing competition in the laundry service sector, Lina Laundry faces challenges in attracting and retaining customers due to limited promotional strategies, an inconvenient location, and conventional facilities. The aim of this study is to analyze the impact of these factors on customer purchasing decisions and provide insights for enhancing marketing strategies. Using a quantitative approach with causal research design, the study employed descriptive analysis, validity and reliability testing, classical assumption testing, and regression analysis. Data was collected from 100 respondents through purposive sampling. The results indicate that promotion, location, and facilities significantly influence customer purchase decisions, with the promotion having the strongest impact. The findings suggest that a strategic combination of promotional activities, optimal location, and improved facilities can enhance customer satisfaction and increase competitiveness. These insights are expected to guide marketing strategies for similar businesses in the service sector.